FLIP, FANTASI FLIPPED CLASSROOM PADA WHATSAPP DAN COLOUR NOTE MENULIS CERITA FANTASI MASA PANDEMI - sumirah; Rahayu Pristiwati; Subyantoro H. Banawa (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
This study aims to describe the activity of 7th grade junior high school students writing fantasy story texts during the covid-19 pandemic via whatsapp and color notes using the Flipped Classroom learning model. The method that the writer uses in this research is descriptive quantitative. This study uses an online classroom action research procedure with whatsApp learning media and color notes. The subject of this research is the students' writing skills of fantasy story texts. The research data collection technique used test and non-test techniques consisting of observation of student activity and interviews, journals, and documentation. The results showed an increase in test results by 22%, from 76.4 in cycle 1 to 88.43 in cycle 2. In addition, the learning process and student behavior became more active, creative, and confident.